Naga Beliefs and Aquatic Culture in the Chao Phraya River Basin: Perspectives from the Royal Irrigation Department: Naga Beliefs and Aquatic Culture in the Chao Phraya River Basin: Perspectives from the Royal Irrigation Department - Vongburee , Bureerat; Yanthong, Thanad (RATANABUTH JOURNAL, 2026)
This research aimed to: 1) study cultural knowledge related to Naga beliefs, and 2) examine the concrete and abstract dimensions associated with belief systems and relationships concerning the Naga, leading to the interpretation of the Royal Irrigation Department’s emblem. The informants were selected through purposive sampling and consisted of three groups: 1) key informants, including local community members and cultural leaders; 2) practitioner informants, including academics and experts, particularly scholars in anthropology and cultural studies; and 3) general informants, including personnel from water-related agencies, especially officials of the Royal Irrigation Department. This study employed a qualitative cultural research approach. Data collection instruments included surveys, interviews, observations, focus group discussions, and workshops. The findings revealed that: 1) Naga beliefs functioned as a body of cultural knowledge that connected belief systems, ways of life, and water management in the Chao Phraya River Basin. They served to establish value frameworks, foster conservation awareness, promote cooperation between the state and communities, and support sustainable water resource utilization in contemporary Thai society. 2) The beliefs and relationships concerning the Naga, as interpreted through the Royal Irrigation Department’s emblem, reflected that the Naga held both concrete and abstract meanings that were systematically interconnected. It functioned as a cultural symbol representing the relationship among humans, water, nature, and society. Key informants, practitioners, and the general public valued the Naga as a guardian of water sources, a symbol of abundance, and a source of spiritual support. This symbolic interpretation reflected the role of the Royal Irrigation Department in sustainably managing water resources based on Thai cultural foundations